2008
DOI: 10.1093/her/cym065
|View full text |Cite
|
Sign up to set email alerts
|

Developing tailored immunization materials for concerned mothers

Abstract: The objectives of this study were to (i) identify 'Worried' and 'Fencesitter' mothers through the use of screening questions; (ii) obtain detailed information from participants about their attitudes and beliefs regarding vaccines and their interactions with their child's main health care provider, including availability of immunization information; (iii) solicit comments on draft educational materials that were developed specifically for this study and (iv) solicit comments on revised educational materials. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 17 publications
1
65
0
Order By: Relevance
“…20 For VHPs, barriers to vaccination have been well described, 13,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and most barriers are centered on concerns about vaccine safety. Surveys or interviews conducted with VHPs have found that VHPs are more likely to state that vaccines are not safe.…”
Section: Barriers To Vaccinationmentioning
confidence: 99%
“…20 For VHPs, barriers to vaccination have been well described, 13,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and most barriers are centered on concerns about vaccine safety. Surveys or interviews conducted with VHPs have found that VHPs are more likely to state that vaccines are not safe.…”
Section: Barriers To Vaccinationmentioning
confidence: 99%
“…Although these items are no substitute for effective communication between concerned parents and HCPs, they help raise awareness of the consequences of refusing immunization, such as outbreaks with sometimes fatal outcomes of diseases such as pertussis, measles, and Haemophilus influenzae type B. 26,[50][51][52] It is fortunate that these outbreaks are not common in the context of high background immunization rates. In addition, research is ongoing to develop tailored immunization materials that may be helpful in improving immunization rates in certain groups of vaccine-hesitant parents.…”
Section: Provide Other Information Resourcesmentioning
confidence: 99%
“…In addition, research is ongoing to develop tailored immunization materials that may be helpful in improving immunization rates in certain groups of vaccine-hesitant parents. 52,53 …”
Section: Provide Other Information Resourcesmentioning
confidence: 99%
“…4 Results of several studies have suggested that mothers do not feel they have sufficient information about immunization. [5][6][7] The traditional Vaccine Information Statements (VIS), which providers are required by law to provide to parents (National Childhood Vaccine Injury Act of 1986), have been criticized for their high reading level and for containing insufficient information. 8 Therefore, efforts have been made to evaluate additional informational materials to supplement VIS.…”
mentioning
confidence: 99%